2014
DOI: 10.1080/09518398.2014.916014
|View full text |Cite
|
Sign up to set email alerts
|

Burdens too difficult to carry? A case study of three academically able Indigenous Australian Masters students who had to withdraw

Abstract: Previous research into attrition rates of Indigenous Australian Higher Degree by Research (HDR) candidates has focused on institutional barriers, highlighting cultural disparities. This case study of three academically able candidates who withdrew before completion from an institution designed to meet the needs of Indigenous students describes their path into the award and non-academic factors over the span of their education that impacted on their performance, then draws upon studies of resilience to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…The differences between Western and Indigenous knowledge systems in the hidden curriculum could turn attending university into a culturally and socially isolating experience for many Indigenous students (Barney, 2013;Pechenkina et al, 2011), leading to a lack of cultural safety for them. The problem exacerbates when overall a very small pool of Indigenous students makes it to university (Chirgwin, 2014).…”
Section: Barriers To Participation In Higher Educationmentioning
confidence: 99%
“…The differences between Western and Indigenous knowledge systems in the hidden curriculum could turn attending university into a culturally and socially isolating experience for many Indigenous students (Barney, 2013;Pechenkina et al, 2011), leading to a lack of cultural safety for them. The problem exacerbates when overall a very small pool of Indigenous students makes it to university (Chirgwin, 2014).…”
Section: Barriers To Participation In Higher Educationmentioning
confidence: 99%
“…Relatedly, for both Indigenous students in secondary school and those who have entered university, economic forms of support, such as scholarships and industry partnerships, have been identified as incentives, with knowledge of these schemes similarly found to be important (Hossain et al 2008;Kinnane et al 2014). Alternative entry pathways to university were also identified (Bandias et al 2014;Chirgwin 2014;Fleet et al 2012;Fredericks et al 2015;Kinnane et al 2014;Shah and Widin 2010) but, interestingly, only within studies that focused on Indigenous students already enrolled in university. A number of these studies suggest that students have utilised these routes to gain access to university, although no studies addressed school students' knowledge of these avenues.…”
Section: Enablers To Pursuing Aspirations and Accessing Higher Educationmentioning
confidence: 99%
“…Intergenerational experiences, as well as one's own past experiences with educational institutions (Harrison 2004;Oliver et al 2013;Toombs and Gorman 2010), physical and mental health issues (Chirgwin 2014;Rigby et al 2010;Toombs and Gorman 2010), and financial concerns (Aseron et al 2013b;Asmar et al 2015;Bandias et al 2014;Ellender et al 2008;Fleet et al 2007;Hillman 2005;Kinnane et al 2014;Morgan 2001;Oliver et al 2013;Rigby et al 2010;Toombs and Gorman 2010;Trudgett 2009;Usher et al 2005) have also been found to impact on retention. For some students, it might 'just not be the right time' to study at university (Fredericks et al 2015).…”
Section: Barriers To Participation Retention and Completion In Highmentioning
confidence: 99%
See 2 more Smart Citations